Polychromy in Ancient Greek Sculpture: New Scientific Research on an Attic Funerary Stele at the Metropolitan Museum of Art - Elena Basso; Federico Carò; Dorothy H. Abramitis (Applied Sciences, 2023)
Polychromy in Ancient Greek Sculpture was the subject of the exhibition Chroma: Ancient Greek Sculpture in Color, held at The Metropolitan Museum of Art (The Met), New York, in 2022–2023. On this occasion, a multidisciplinary project involving The Met’s Departments of Greek and Roman Art, Objects Conservation, Imaging, Scientific Research, and colleagues from the Liebieghaus Polychromy Research Project in Frankfurt, Germany, was carried out to study an Attic funerary monument. The color decoration of the sphinx was reconstructed by combining non-invasive and minimally invasive techniques that provided information about surviving and lost pigments, original design, and painting technique. Results of multiband imaging, digital microscopy, and X-ray fluorescence spectroscopy guided the removal of minute samples from selected areas for examination by Raman spectroscopy and scanning electron microscopy, coupled with energy-dispersive X-ray spectroscopy, to shed light on the pigments and paint stratigraphy. The color palette included two varieties of blue, Egyptian blue and azurite, a carbon-based black pigment, two reds, cinnabar and red ocher, and yellow ocher, all painted directly over the marble without a preparation layer. The scientific findings informed the physical reconstruction of the sphinx made by archaeologists from the Liebieghaus Polychromy Research Project, featured in the exhibition.